2017
DOI: 10.1002/mrd.22843
|View full text |Cite
|
Sign up to set email alerts
|

miR‐100 promotes the proliferation of spermatogonial stem cells via regulating Stat3

Abstract: Micro RNAs play important roles during mammalian spermatogenesis, but the function(s) of specific miRNAs remain largely unknown. Here, we report that miR-100 is predominantly expressed in undifferentiated murine spermatogonia, including spermatogonial stem cells (SSCs). We utilized a miRNA mimic and inhibitor to knock down and overexpress miR-100 in cultured SSCs, respectively, finding that the miR-100 promotes the proliferation of SSCs in vitro. Furthermore, signals promoting SSC maintenance induced, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…MiRNAs are globally expressed in the murine testis, and numerous miRNAs play vital roles in spermatogenesis, especially SSC development10. For example, miR-34b/c and miR-449a/b/c are important for normal spermatogenesis and male fertility, and knockout of miR-34b/c and miR-449 leads to infertility because of severe spermatogenic disruptions11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs are globally expressed in the murine testis, and numerous miRNAs play vital roles in spermatogenesis, especially SSC development10. For example, miR-34b/c and miR-449a/b/c are important for normal spermatogenesis and male fertility, and knockout of miR-34b/c and miR-449 leads to infertility because of severe spermatogenic disruptions11.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-34b/c and miR-449a/b/c are important for normal spermatogenesis and male fertility, and knockout of miR-34b/c and miR-449 leads to infertility because of severe spermatogenic disruptions11. MiR-100 is highly expressed in SSCs, and miR-100 promotes SSC proliferation via Stat310. MiR-17-92 is a critical player in normal spermatogenesis of mice, and disruption of miR-17-92 suppresses sperm production because of the reduced number of SSCs12.…”
Section: Introductionmentioning
confidence: 99%
“…For examples, miR‐29 and miR‐252 were predicted to target Wnt4 (Liu, Feng, et al, 2019), miR‐446i and miR‐3574 targeted Six4 and Six5 , the key regulators of gonadal development (Fujimoto et al, 2013; Kirby et al, 2001), respectively (Table 2). Previous studies showed that the sex‐biased miR‐184 and miR‐100 function in speeding up the proliferation of the germ cell line in mouse testis (Huang et al, 2017; Wu et al, 2011). Similarly, the miR‐184 and miR‐100 were also predominantly expressed in testis of the Chinese mitten crab E. sinensis like the swimming crab P. trituberculatus and the mud crab S. paramamosain (Figure 3; Jia et al, 2018; Meng et al, 2018), suggesting that miR‐184 and miR‐100 could have conserved roles in testicular development.…”
Section: Discussionmentioning
confidence: 99%
“…If differentiation prevailed, stem cells would deplete themselves, inducing seminiferous lumens with only the supporting Sertoli cells. Cumulating evidence has demonstrated that GDNF, Lin28a, Dmrt1, B7-H3 and miR-100 promote SSC proliferation [38][39][40][41][42], while miR-204 and Mir146a suppress SSC proliferation [43,44]. During cell cycle, Cyclindependent kinases (CDKs) and their regulatory binding partners, cyclins, comprise the central machinery and promote cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%